Penerapan Metode AHP-SAW dalam Sistem Pendukung Keputusan Pemilihan Desa Wisata Terbaik - Ni Ketut Ayu Purnama Sari (Jurnal Teknik Informatika C.I.T Medicom, 2021)
From the perspective of advanced tourism growth, Indonesia's economy is expected to enter the top ten in the world by 2025 before the 2020 COVID-19 pandemic. Balinese workforce absorbs nearly a third of the total population and Balinese are involved in tourism. Garbage and congestion are problems the government must solve in building a better Bali tourism industry in the future. One way to solve this problem is to develop rural ecotourism, which can choose to use a decision support system. In this study, the method used was a combination of AHP-SAW. This manual DSS calculation process can be implemented in web-based software. DSS employs 3 tourists as decision maker. There are 10 alternative tourism villages tested using AHP-SAW, and the tourist villages produced by Pemuteran are the most popular tourist villages. Pemuteran Tourism Village obtained a score of 0.9241. Jatiluwih Tourism Village obtained a score of 0.9117 in second place; Plaga Tourism Village obtained a score of 0.9115 in third place.